(1/2)^2 divide 0.05+(-3/4*8/3) and the other 2(7/8-1/4)-(-1.5)^2

(1/2)^2 divide 0.05+(-3/4*8/3)

= 1/4 ÷ 0.05+ (-3/4*8/3) [because 1/2 * 1/2 = 1/4 (you multiply top 2 numbers and bottom 2 numbers)]

= 0.25 ÷ 0.05 +(-3/4*8/3) [because 1/4 = 0.25]

= (25 ÷ 5) + (-3/4*8/3) getting rid of decimals

= 5 + (-3/4*8/3) Do the division now and then the fractions in the brackets

= 5 + (-24/12) (multiply top 2 numbers and bottom 2 numbers of the fraction)

= 5 + -2 because -24 ÷ 12 = -2)

= 3

2(7/8-1/4)-(-1.5)^2

=2(7/8-2/8) -(1.5)^2 (1/4 = 2/ 8 and a negative number squared is the same as a positive number squared )

= 2* 5/8 - 2.25 ( 1.5 squared = 2.25_)

= 10/8 - 2.25

= 5/4 - 2.25

= 1.25 - 2.25

=1

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up